Dental insurance, service use and health outcomes in Australia: a systematic review. (11th September 2017) - Gnanamanickam, ES; Teusner, DN; Arrow, PG; Brennan, DS
Abstract: Private health insurance plays a key role in financing dental care in Australia. Having private dental insurance has been associated with higher levels of access to dental care, visiting for a check‐up and receiving a favourable pattern of services. Associations with better oral health have also been reported. In the absence of any existing review, this paper aims to systematically review the relationship between dental insurance and dental service use and/or oral health outcomes in Australia. A systematic search of online databases and subsequent sifting resulted in 36 publications, 33 of which were cross sectional and three cohort analyses. Dental service outcomes were more commonly reported than oral health outcomes. There was considerable heterogeneity in the outcome measures reported, for both service use and health outcomes. Overall, the majority of the evidence was from cross sectional studies and few studies reported analyses adjusted for confounding factors. The consolidated evidence points towards a positive association between dental insurance and dental visiting. Dentally insured adults are likely to have more regular access to dental care and have a more favourable pattern of service use than the uninsured. However, evidence of associations between dental insurance and oral health are mixed.